Penggunaan Pemasaran Digital (Digital Marketing) Sebagai Pendukung Pengembangan Usaha Pada Kelompok Pengrajin Anoa Art - Patta Hindi Asis; Marjani Marjani; Andi Awaluddin Ma’ruf (Ilin Institute, 2020)
The purpose of this PKM is to overcome the problems of partners by implementing digital marketing and fostering innovation in economic value products so that their craft products can reach a broad target market. Through a participatory approach, the implementation of activities in the group of craftsmen together collaborate to find solutions using digital marketing methods of craft products. Collaboration uses multi-stakeholder campuses, partner groups, professionals, and the government in formulating and finding solutions to the problems of craftsmen groups in the village of Pangan Jaya. As a result, using online marketing through the website, whatsapp messaging applications, facebook and Instagram products sold significantly increased and marketing of craft products has reached a wider market.